Integrating Social Values: Evidence from The Intermediary Institution in Indonesian Elections - Tawakkal, George Towar Ikbal (Politika: Jurnal Ilmu Politik, 2022)
Many scholars called the intermediary institutions in elections as vote brokers. As a consequence of that, then they built an argument based on a transactional framework, especially about the motivation of the institution. On the other side, they agreed that vote brokerage was built based on a social network, especially when they tried to define the vote brokerage. It means, the intermediary institution occurred in social interactions. That is weird for explaining social interactions without considering other social values. It looks like social interaction is only about material value. Other scholars tried to be fairness by calling the intermediary as middlemen, but still very few literature built the argument based on a non-transactional framework. This study will certainly provide new insights into the intermediary institution studies, particularly related to the understanding of non-transactional amid transactional arguments that have been shown in many kinds of literature, as well as expanding the study of intermediary institutions which likely to focused on providing voters, to be focused on the establishment of intermediary institutions. We conducted a series of in-depth interviews with 45 people consisting of persons in the intermediary institutions, political party leaders, leaders of campaign teams, election organizers, and more than a hundred voters during 2017 – 2019 in Indonesian elections, consists of four Villages head elections, 2018 Governor election, and 2019 legislative elections. We found the transactional logic or material value was not the only one, even mostly was not the dominant value that generated the intermediary institutions.